RANCANG BANGUN TURBIN UAP PADA MAKET PEMBANGKIT LISTRIK TENAGA UAP - Muhamad Rizky Septianto; Massus Subekti; Daryanto (Fakultas Teknik Universitas Negeri Jakarta, 2017)
The purpose of this study was to produce a prototype steam turbine at maket power plant steam generator torque that can play. The research method used in this research is descriptive analysis by type of engineering. Steam turbine is a Primemover that converts potential energy into mechanical energy in the form of rotation of the turbine shaft. Steam turbine constructed dimensions turbine type used single stage impulse turbine, turbine disc diameter of 33mm, the amount of movement of the blade 30 pieces, the distance between the blade 14,6mm, radious 2,63mm blade, the type of nozzle used convergent, area 3,2cm2 neck cross-section, the cross sectional area of 3,2cm2 side exit. Mockups of the steam turbine can generate 1490 rpm for turbine with a steam generator at a pressure of 4 kg/cm2 using a water volume of 19 liters. Maximum pressure that can be accepted by the steam turbine is 8 kg/cm2 with 11.000rpm, produced according to the process of heating boiler which is the maximum vapor pressure of 8kg/cm2 at a temperature of 1700C. and and be able to turn a generator with a torque of 4.6 Nm with a pressure of 8 kg/cm2 The conclusion of this study is the turbine can be built through the calculations have been carried out and taking into account the performance of the boiler and steam generator.Turbin built to produce 1336.6 rpm to spin the turbine without the steam generator at a pressure of 2 kg / cm2. Steam turbines are built to produce 1408 rpm, and generates a voltage 140.8 volts, and be able to play generatoe torque of 0.6 Nm for turbine with the steam generator at a pressure of 4 kg / cm2. Maximum pressure received by the steam turbine is 8 kg / cm2 at 10 453 rpm for the turbine without a generator, and a voltage of 271.8 volts produces, as well as being able to roll generatoe torque of 0.9 Nm for turbine with a generator on the vapor pressure of the incoming sebesae 8 kg / cm2. Abstrak Tujuan dari penelitian ini adalah untuk menghasilkan prototipe turbin uap yang mampu memutar torsi generator. Metode penelitian yang dipakai dalam penelitian ini adalah analisis deskriptif dengan jenis rekayasa teknik. Turbin uap (steam turbine) adalah penggerak mula yang merubah energi potensial menjadi energi mekanis dalam bentuk putaran poros turbin. Turbin uap yang dibangun memiliki dimensi jenis turbin yang digunakan turbin impuls single stage, cakram turbin berdiameter 33 mm, jumlah sudu gerak 30 buah, jarak bagi antar sudu 14,6mm, jari–jari sudu 2,63mm, jenis nosel yang digunakan konvergen, luas penampang leher 3,2cm2, luas penampang sisi keluar 3,2cm2. Maket turbin uap tersebut dapat menghasilkan 1490 rpm untuk putaran turbin dengan generator pada tekanan uap 4 kg/cm2 menggunakan volume air 19 liter. Tekanan maksimal yang mampun diterima oleh turbin uap ini adalah 8 kg/cm2 dengan 11.000rpm, sesuai yang dihasilkan pada proses memanasan boiler yaitu tekanan uap maksimalnya adalah 8kg/cm2 pada suhu 170oC. serta mampu memutar generator dengan torsi 4,6 N dengan tekanan 8 kg/cm2. Kesimpulan dalam penelitian ini adalah turbin dapat dibangun melalui perhitungan yang telah dilakukan dan dengan mempertimbangkan unjuk kerja antara boiler dan generator.Turbin uap yang dibangun dapat menghasilkan 1336,6 rpm untuk putaran turbin tanpa generator pada tekanan uap 2 kg/cm2. Turbin uap yang dibangun dapat menghasilkan 1408 rpm, dan menghasilkan tegangan 140,8 volt, serta mampu memutar torsi generatoe sebesar 0,6 Nm untuk putaran turbin dengan generator pada tekanan uap 4 kg/cm2. Tekanan maksimal yang diterima oleh turbin uap ini adalah 8 kg/cm2 dengan 10.453 rpm untuk putaran turbin tanpa generator, dan menghasilkan tegangan 271,8 volt, serta mampu memutar torsi generatoe sebesar 0,9 Nm untuk putaran turbin dengan generator pada tekanan uap yang masuk sebesae 8 kg/cm2.